2010
DOI: 10.1186/1471-2458-10-601
|View full text |Cite
|
Sign up to set email alerts
|

What happens to ART-eligible patients who do not start ART? Dropout between screening and ART initiation: a cohort study in Karonga, Malawi

Abstract: BackgroundRoutine ART programme statistics generally only provide information about individuals who start treatment. We aimed to investigate the outcome of those who are eligible but do not start ART in the Malawi programme, factors associated with this dropout, and reasons for not starting treatment, in a prospective cohort study.MethodsIndividuals having a first screening visit at the ART clinic at Karonga District Hospital, northern Malawi, between September 2005 and July 2006 were interviewed. Study follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 17 publications
3
38
1
Order By: Relevance
“…Studies from a variety of African settings have found that personal and provider barriers to ART initiation include stigma and denial of need for ART, lack of symptoms (which could decrease motivation to initiate life-long therapy), fear of ART side effects, transportation costs, lengthy pre-treatment processing, and lack of access to CD4 testing [7–10]. Understanding factors associated with ART-eligible individuals delaying or declining treatment will inform how to improve retention in pre-ART care, reduce HIV-associated morbidity, and help design strategies to motivate treatment initiation at higher CD4 counts, particularly as treatment guidelines evolve towards treating earlier in the course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from a variety of African settings have found that personal and provider barriers to ART initiation include stigma and denial of need for ART, lack of symptoms (which could decrease motivation to initiate life-long therapy), fear of ART side effects, transportation costs, lengthy pre-treatment processing, and lack of access to CD4 testing [7–10]. Understanding factors associated with ART-eligible individuals delaying or declining treatment will inform how to improve retention in pre-ART care, reduce HIV-associated morbidity, and help design strategies to motivate treatment initiation at higher CD4 counts, particularly as treatment guidelines evolve towards treating earlier in the course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the pre-ART period is highlighted here, as elsewhere, by the finding that about 21% of all programmatic deaths in our cohort occurred prior to the initiation of ART [18–20]. As has been pointed out by others, if pre-ART deaths are not included in routine programme reporting, then overall programme outcomes may appear misleadingly favourable [3,5]. Principally this is because those with more advanced disease are more likely to die in the pre-ART period, with those commencing ART having a relative survival advantage.…”
Section: Discussionmentioning
confidence: 57%
“…Although we cannot establish the underlying reasons for this in our cohort, a study in Malawi within which similar numbers of eligible patients failed to commence ART, found 58% of such patients to have died [3,17]. Patients who do not die may return at a later stage with more advanced disease whereas some may have re-registered for HIV care elsewhere.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations